Prevalence of COPD in Spain: impact of undiagnosed COPD on quality of life and daily life activities. Issue 10 (23rd June 2009) - Miravitlles, M; Soriano, J B; García-Río, F; Muñoz, L; Duran-Tauleria, E; Sanchez, G; Sobradillo, V; Ancochea, J
Abstract : Aims: This study aimed to determine the prevalence of chronic obstructive pulmonary disease (COPD) in Spain and identify the level of undiagnosed disease and its impact on health-related quality of life (HRQL) and activities of daily living (ADL). Methods: A population-based sample of 4274 adults aged 40–80 years was surveyed. They were invited to answer a questionnaire and undergo prebrochodilator and postbronchodilator spirometry. COPD was defined as a postbronchodilator FEV1 /FVC (forced expiratory volume in 1 s/forced vital capacity) ratio of <0.70. Results: For 3802 participants with good-quality postbronchodilator spirometry, the overall prevalence of COPD was 10.2% (95% CI 9.2% to 11.1%) and was higher in men (15.1%) than in women (5.6%). The prevalence of COPD stage II or higher was 4.4% (95%CI; 3.8%–5.1%). The prevalence of COPD increased with age and with cigarette smoking and was higher in those with a low educational level. A previous diagnosis of COPD was reported by only 27% of those with COPD. Diagnosed patients had more severe disease, higher cumulative tobacco consumption and more severely impaired HRQL compared with undiagnosed subjects. However, even patients with undiagnosed COPD stage I+ already showed impairment in HRQL and in some aspects of ADL compared with participants without COPD. Conclusions: The prevalence of COPD in individuals between 40 and 80 years of age in Spain is 10.2% and increases with age, tobacco consumption and lower educational levels. The rate of diagnosised COPD is very high and undiagnosed individuals with COPD already have a significant impairment in HRQL and ADL.